Structural basis of Iridoid synthase mediated cyclization of 10-oxogeranial - Sandholu, Anandsukeerthi; H. V. Thulasiram; Sengupta, Jayati; Kulkarni, Kiran (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Cryo-EM; iridoid synthase; Single Particle reconstruction

Data on the effect of oral feeding of Arachidonic acid or Docosahexanoic acid on haematopoiesis in mice - Limbkar, K. (Data in Brief, 2017)
Stem cells have peculiar property to self-renew and differentiate. It is important to control their fate in safe and effective ways for their therapeutic use. The mediators of essential polyunsaturated fatty acids (PUFAs) namely Arachidonic acid (AA) and Docosahexanoic acid (DHA) are known to play a role in haematopoiesis via various metabolic pathways [1]. However the direct effect of purified AA or DHA on haematopoiesis has not been well investigated yet. We have reported that oral administration of PUFAs enhanced haematopoiesis in mice [2]. Signaling Leukocyte Antigen Molecule (SLAM) (CD48−CD150+) phenotype consists of pure population of haematopoietic stem cells (HSCs). Herein we observed higher percentage of SLAM (CD48−CD150+) phenotype in the bone marrow (BM) cells of mice fed with AA or DHA compared to PBS fed control mice. Data from engraftment study depicts that BM from AA/DHA-fed mice showed higher absolute number of donor cells in recipient mice compared to control. The enhanced hematopoiesis observed in AA/DHA-fed mice was returned to normal when the mice were kept on normal diet for six weeks (after ten days of oral feeding). We confirmed GCMS (Gas Chromatography-Mass Spectroscopy) retention times of AA and DHA by co-injecting fatty acid extract from AA or DHA fed mice with purified AA or DHA standards respectively. Representative flow cytometry profile of Lin−Sca-1+c-kit+(LSK) cells showed higher expression of CXCR4 protein and ligands of Wnt, Notch1 signaling in BM of AA/DHA-fed mice

Methylglyoxal attenuates insulin signaling and downregulates the enzymes involved in cholesterol biosynthesis - Deshmukh, Arati B.; Bai, Shakuntala; Aarthy, T.; Kazi, Rubina S.; Banarjee, Reema; Rathore, Rajeshwari; Vijayakumar, M. V.; H. V. Thulasiram; Bhat, Manoj Kumar; Kulkarni, Mahesh J. (Molecular Biosystems, 2017)
Methylglyoxal (MG) is a highly reactive dicarbonyl known to be elevated under the hyperglycemic conditions of diabetes and is implicated in the development of diabetic complications. Therefore, the current study investigates the role of MG in exacerbating insulin resistance at the insulin signaling level, as well as its effect on the global proteomic level. By using insulin sensitive rat muscle cells (L6) and Chinese hamster ovary (CHO) cells stably expressing the insulin receptor (IR) and a glucose transporter fused with green fluorescent protein (GLUT4-GFP), we have observed that MG impairs insulin signaling, inhibits GLUT4 translocation and reduces glucose uptake. SWATH MS analysis, a label-free quantitative mass spectrometric approach, showed altered expression of 99 proteins out of 2404 identified in response to MG treatment. These proteins are mainly involved in stress response, protein folding and proteolysis. Some of the deregulated proteins such as thioredoxin 2, glutathione S transferase, T complex protein 1 subunit beta (tcbp1), heat shock protein 90 and E3 ubiquitin ligase were previously reported to be associated with either diabetes or insulin resistance. Interestingly, aminoguanidine (AMG), a potent dicarbonyl scavenger, restored the deleterious effects of MG. For the first time, we report that MG induces downregulation of enzymes involved in cholesterol biosynthesis such as acetyl-CoA acetyltransferase, hydroxymethylglutaryl-CoA synthase, farnesyl pyrophosphate synthetase, squalene monooxygenase, and lanosterol synthase. GC MS analysis for sterol metabolites corroborated the proteomic results; MG significantly reduced cholesterol production whereas AMG treatment restored cholesterol production to levels similar to the control. Thus, MG leads to primary defects in insulin signaling and cellular abnormalities at the proteomic and metabolic levels, both of which may contribute to the development of insulin resistance.

De novo transcriptome analysis of the egg parasitoid Trichogramma chilonis Ishii (Hymenoptera: Trichogrammatidae): a biological control agent - Kerima, O.Z.; Niranjana, P.; Vinay Kumar, B.S.; Ramachandrappa, R.; Puttappa, S.; Lalitha, Y.; Jalali, S.K.; Ballal, C.R.; H. V. Thulasiram (Gene Reports, 2018)
Trichogramma chilonis Ishii is an endoparasitic wasp widely used as a biological control agent of economically important pests. However, absence of genetic information on T. chilonis hampers further research, especially at the molecular level. Here, we performed the first RNA-Seq of the adult T. chilonis. A total of 18,372,639 high-quality reads were generated using Illumina pair-ended sequencing platform. De novo assembly resulted into 24,488 transcripts, with mean length and N50 values of 1444.2 bp and 2667 bp, respectively. Of the transcripts, 14,643 exhibited putative homology with class Insecta proteins from UniPROT database. To understand the contig functions, gene descriptions, gene ontology and cluster of orthologous group annotations were analyzed. Following functional annotation, a number of transcripts encoding detoxification, target receptor action and olfaction- related proteins were identified and analyzed. In addition, 4520 transcripts containing simple sequence repeats, ranging from dinucleotide to hexanucleotide repeats were discovered, with trinucleotide being the most enriched repeats. This new sequence resource will shed light on various molecular mechanisms in T. chilonis and related species.